The role of coach-athlete relationship quality in team sport athletes` psychophysiological exhaustion: implications for physical and cognitive performance - Davis, L.; Appleby, R.; Davis, P.; Wetherell, M.; Gustafsson, H. (Journal of Sports Sciences, 2018)
The present study aimed to examine associations between the quality of the coach-athlete relationship and athlete exhaustion by assessing physiological and cognitive consequences. Male and female athletes (N = 82) representing seven teams across four different sports, participated in a quasi-experimental study measuring physical performance on a 5-meter multiple shuttle test, followed by a Stroop test to assess cognitive performance. Participants provided saliva samples measuring cortisol as a biomarker of acute stress response and completed questionnaires measuring exhaustion, and coach-athlete relationship quality. Structural equation modelling revealed a positive relationship between the quality of the coach-athlete relationship and Stroop performance, and negative relationships between the quality of the coach-athlete relationship and cortisol responses to high-intensity exercise, cognitive testing, and exhaustion. The study supports previous research on socio-cognitive correlates of athlete exhaustion by highlighting associations with the quality of the coach-athlete relationship.